2021
DOI: 10.1108/ijbm-04-2020-0209
|View full text |Cite
|
Sign up to set email alerts
|

Linking corporate social responsibility to trust in the banking sector: exploring disaggregated relations

Abstract: PurposeThis paper has two purposes. First is to operationalise the concepts of corporate social responsibility (CSR) and trust in the context of a developing country, the Democratic Republic of Congo (DRC). Second purpose is to test in a disaggregated perspective the impact of each CSR dimension on trust.Design/methodology/approachData were collected from 264 customers of six banks and processed with exploratory, confirmatory factor analysis and structural equations using LISREL 9.1.FindingsCSR is found to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 97 publications
(137 reference statements)
5
52
0
Order By: Relevance
“…It has been shown that, in the case of negative information, the negative effect will be evident in consumer attitudes, who are more sensitive to negative information than in the positive one (Sen and Bhattacharya 2001 ). The findings are in line with previous studies of the CSR and sustainability literature for the banking sector (Bugandwa et al 2021 ). They identified that some strategies of CSR play a critical role in the customer trust such as legal compliance, social norms, product responsibility, environmental protection, and employee relations.…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that, in the case of negative information, the negative effect will be evident in consumer attitudes, who are more sensitive to negative information than in the positive one (Sen and Bhattacharya 2001 ). The findings are in line with previous studies of the CSR and sustainability literature for the banking sector (Bugandwa et al 2021 ). They identified that some strategies of CSR play a critical role in the customer trust such as legal compliance, social norms, product responsibility, environmental protection, and employee relations.…”
Section: Discussionsupporting
confidence: 93%
“…With the increasing number of banks implementing CSR programs, CSR has been considered a prominent concept in academia. However, the majority of CSR studies have focused on "external stakeholders" (customers), and less attention has been paid to "internal stakeholders" (employees) (Bugandwa et al, 2021). Furthermore, except for Kim et al (2016), who conducted research in a casino setting and called for more studies to examine the effects of both CSR and IM on service employees simultaneously, no study has empirically examined the simultaneous effects of both CSR and IM practices on banking employees' job outcomes.…”
Section: Customer-oriented Boundaryspanning Behaviormentioning
confidence: 99%
“…With the increasing number of banks implementing CSR programs, CSR has been considered a prominent concept in academia. However, the majority of CSR studies have focused on “external stakeholders” (customers), and less attention has been paid to “internal stakeholders” (employees) (Bugandwa et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Investor confidence has been affected worldwide by multiple cases of financial frauds observed in the last decade in world-renowned companies (Bugandwa et al, 2021). Under this environment, companies try to develop and implement policies and strategies to grow, consolidate and sustain themselves over time (Arrigoni, 2019).…”
Section: Introductionmentioning
confidence: 99%